Sistem Monitoring Meteorologi Menggunakan Mikrokontroler Berbasis Web - Romi Wiryadinata; Andhika Raharja Mukti; Rian Fahrizal (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
Indonesia is an area of tropical islands with a tropical wet (humid tropic) which has two seasons of the dry season that occurred in May to October and the rainy season in November to April. In meteorological data monitoring system many of the facilities used include using thingspeak that can be accessed online and realtime wherever and whenever connected to the internet. The purpose of this research is to make monitoring system of meteorological sensor data in realtime by using data logger which is stored in thingspeak server using Android platform, Windows, iOS. The input of this research comes from meteorological sensor which is then processed using a microcontroller in the form of serial data so that it can be sent to the network which will be connected to thingspeak.com. On the Android platform the application is used thingsview, while on IOS using TS Connect application and on Windows using googlechrome, mozzila firefox or browser available on the PC client. The website address used on the Windows platform is https://thingspeak.com/channels/358620. Monitoring results have values corresponding to the data logger. The unsuitable value of the monitoring result is caused by the error that occurs on the sensor.